Primary Metabolism in Citrus Fruit as Affected by Its Unique Structure - Sadka, Avi; Shlizerman, Lyudmila; Kamara, Itzhak; Blumwald, Eduardo (Frontiers in Plant Science, 2019)
Citrus is one of the world's most important fruit crops, contributing essential nutrients, such as vitamin C and minerals, to the human diet. It is characterized by two important traits: first, its major edible part is composed of juice sacs, a unique structure among fruit, and second, relatively high levels of citric acid are accumulated in the vacuole of the juice sac cell. Although the major routes of primary metabolism are generally the same in citrus fruit and other plant systems, the fruit's unique structural features challenge our understanding of carbon flow into the fruit and its movement through all of its parts. In fact, acid metabolism and accumulation have only been summarized in a few reviews. Here we present a comprehensive view of sugar, acid and amino acid metabolism and their connections within the fruit, all in relation to the fruit's unique structure.